2006
DOI: 10.1038/nphys475
|View full text |Cite
|
Sign up to set email alerts
|

Controllable valley splitting in silicon quantum devices

Abstract: Silicon has many attractive properties for quantum computing, and the quantum dot architecture is appealing because of its controllability and scalability. However, the multiple valleys in the silicon conduction band are potentially a serious source of decoherence for spin-based quantum dot qubits. Only when these valleys are split by a large energy does one obtain well-defined and long-lived spin states appropriate for quantum computing. Here we show that the small valley splittings observed in previous exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
261
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(280 citation statements)
references
References 39 publications
18
261
1
Order By: Relevance
“…The effective Landé factor is g = 2. 44,89 Other material parameters read c l = 9150 m/s (for LA phonons), c t = 5000 m/s (for TA phonons), ρ = 2330 kg/m 3 , and ε = 11.9ε 0 . 90 The choice of deformation potential constants is not unique, 83,84,91 and we use d = 5 eV and u = 9 eV according to Ref.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective Landé factor is g = 2. 44,89 Other material parameters read c l = 9150 m/s (for LA phonons), c t = 5000 m/s (for TA phonons), ρ = 2330 kg/m 3 , and ε = 11.9ε 0 . 90 The choice of deformation potential constants is not unique, 83,84,91 and we use d = 5 eV and u = 9 eV according to Ref.…”
Section: Modelmentioning
confidence: 99%
“…This remaining degeneracy is further split if the perpendicular confinement is asymmetric, resulting in an energy difference called the ground-state gap. [42][43][44][45][46][47][48][49] As the valley degeneracy is believed to be the main obstacle for silicon-based quantum computation, 46,50,51 a large valley splitting is desired. If this is the case, the multivalley system can be reduced to an effective single-valley qubit, a potentially nuclear-spin-free analog to the well-known GaAs counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…The multiplicity of the Hilbert space brought about by the existence of equivalent valleys has been shown to hamper spin QC. [71][72][73][74][75] At the same time, the interface potential gives rise to a valley-orbit coupling, which has been studied extensively in recent years, both experimentally [76][77][78][79][80][81] and theoretically. [82][83][84][85][86][87][88][89][90] Addressing specific valley eigenstates is a profound, challenging and unresolved problem.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is no external control of the valley quantum number, complications include difficulty in well-defined initialization and enhanced spin decoherence at valley relaxation "hotspots" [7]. Experimental measurements of the magnitude of the valley splitting between the lowest two valley states include spinvalley "hotspots" [8] and valley splitting magnitude tunable with electric field [7] [9]. The experimental work most relevant for our study is Shi et al [10], which showed experimentally a shift in the single-triplet splitting J for two electrons on a single dot, where J is dominated by the energy difference between single-particle ground and excited valley-orbit states in Si/SiGe.…”
mentioning
confidence: 99%
“…Since the valley phase in Equation 6 arises from the vertical height of the interface, at first glance one might think that moving the dot vertically into the Si substrate might have a strong effect on ∆φ; although a vertical electric field has strong effect on the magnitude of the coupling [9][21] , it has a small effect on ∆φ [15], at least for a flat interface. However, due to the strong dependence of the valley phase on the exact local realization of the interface roughness, using Overall, Figure 3 shows this possibility: the upper panel shows the effect on ∆φ of using a lateral gate voltage to move both dots laterally with a constant separation, for both a sinusoidal interface (∆λ = 0) and random interface (∆λ = 10).…”
mentioning
confidence: 99%